Satisfaction levels of patients and their families with a Psychiatric Hospital Unit - Fernández-Carbonell, Mª José; Dasí, Carmen; García-Merita, Mª Luisa; Fuentes, Inmaculada (Anales de Psicología / Annals of Psychology, 2012)
In recent decades there has been growing interest in examining patient satisfaction since it can have great influence on the patients’ adherence to treatment and their clinical evolution. Similarly, it has been demonstrated that the satisfaction of psychiatric patients is an indicator of the quality of mental health services. It has also been demonstrated that it is a strong predictor of the future use that psychiatric patients will make of these services and their willingness to cooperate with treatment. In Spain, there have been few studies conducted on patient satisfaction in Spanish psychiatric hospital units. This study analyzes the satisfaction levels of in-patients in a psychiatric hospital unit and those of their family members. The results show high levels of overall satisfaction with the services received in the unit. They show particularly high levels of satisfaction with regard to the perceived behavior and competence of the professionals involved and more moderate levels of satisfaction with regard to the information received and opportunities to become involved in the treatment plan. The study also analyzes the influence of social demographic variables and other variables (related to admission, the type of mental illness, and the social functioning of the patient) on the satisfaction levels of psychiatric patients and their family members.